2018
DOI: 10.9740/mhc.2018.09.202
|View full text |Cite
|
Sign up to set email alerts
|

Extent of use of long-acting injectable antipsychotics in children and adolescents within Indiana Medicaid

Abstract: Introduction:Oral formulations of the antipsychotics aripiprazole, asenapine, lurasidone, olanzapine, paliperidone, quetiapine, and risperidone are indicated for use in pediatrics for several diagnoses. Long-acting injectable (LAI) antipsychotics are of interest in this special population because they may be used due to convenience and desire to improve adherence, despite limited support in the literature. The primary intent of this study is to provide descriptive information on the use of paliperidone palmita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Adolescents placed in foster care could be another indicator for considering the use of LAIA, due to a higher risk of non-adherence, and increased incidence of behavioral difficulties and substance use comorbidities [ 73 ]. In fact, youth in foster care comprised 23.3% of the patients included in one of the studies reviewed [ 28 ] and 16% of the children and adolescents with at least one prescription of LAIA in the study conducted in the Indiana Medicaid system [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents placed in foster care could be another indicator for considering the use of LAIA, due to a higher risk of non-adherence, and increased incidence of behavioral difficulties and substance use comorbidities [ 73 ]. In fact, youth in foster care comprised 23.3% of the patients included in one of the studies reviewed [ 28 ] and 16% of the children and adolescents with at least one prescription of LAIA in the study conducted in the Indiana Medicaid system [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Insight is associated with adherence to treatment [ 77 ]. Worse insight has been associated with more severe symptoms, increased risk of discontinuing treatment, and poorer outcomes [ 74 , 78 , 79 ]. Significantly, it has also been suggested that younger patients may have less insight than adults with SSD [ 75 , 76 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…In pediatric populations, oral formulations of second generation antipsychotics (APs) are used in various psychiatric conditions, including schizophrenia, bipolar disorder, and irritability associated with autism-spectrum disorder. 1 Long-acting injectable antipsychotics (LAIAs) demonstrate improved outcomes in adult patients with schizophrenia or bipolar disorder, a population that may particularly struggle with medication adherence. 2–4 The mechanism of LAIAs allows for the release of steady serum concentrations over a longer period of time when compared with oral APs.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Whereas limited studies conclude that there may be improved clinical outcomes and adherence with using LAIAs when compared with oral counterparts, the lack of data supporting LAIA use in this population may lead to lower use of these formulations. 1 A meta-analysis of studies involving pediatric patients with SSD found clinical improvement of patients using LAIA formulations in up to 12 months of follow-up. 6 A retrospective database analysis concluded that, although there is limited clinical data supporting the safety and efficacy of LAIAs in adolescents, their use in patients with documented nonadherence would be appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…Por otro lado, las recomendaciones de dosificación etiquetadas para el uso de LAIAs se basan en poblaciones adultas; por lo tanto, no se conoce la dosificación adecuada para la población pediátrica ni se tienen de datos de seguridad a largo plazo con respecto efectos adversos. Además, no existen datos farmacocinéticos publicados para antipsicóticos LAI en la población pediátrica, lo que lleva a algunas incógnitas como si las diferencias en la masa muscular podrían alterar la liberación o distribución de los antipsicóticos LAI actualmente disponibles (4).…”
Section: Introductionunclassified